1987
DOI: 10.1149/1.2100635
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Behavior in Aqueous Media of Conducting Polymers: II . The Insoluble Fractions Obtained on the Cu(II) Catalyzed Polymerization of (2,5‐Dibromo‐3‐Group IV Substituted) Thiophenes

Abstract: The chemical polymerization of (2,5-dibromo-3-substituted) thiophenes utilizing Cu(II)C12 as a copromoter yields an amorphous insoluble polymer fraction which exhibits a very high electronic conductivity varying between 10 -1 to 102 S-cm. These materials have been used as electrode materials. The redox chemistry of the Cu(II) containing polymer in contact with supporting electrolyte only shows a distinct internal (Cu(II)/Cu(I) cyclic voltammetric wave. No redox behavior for the thiophene ring system is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…34 The high hydrophobicity of the color-tuned 2D-NF surfaces is highly advantageous in their practical applications because π-electronic molecules, and the performance of devices based on such molecules, are influenced significantly by environmental exposure to moisture, which generally causes chemical degradation and a sharp decrease in physical stability. 35,36 Another noteworthy feature is that, when we adopted a modified soft deposition technique, 37 a thicker fabric consisting of multiple layers of different kinds of 2D-NFs could be obtained. Such heterogeneous multilayered 2D-NFs are known to be difficult to fabricate, in cases of general multilayer films or assemblies of π-electron molecules, by solution processes such as drop-casting and spin-coating techniques.…”
Section: Conformation Change Of Cn-tfmbe Molecules Duringmentioning
confidence: 99%
“…34 The high hydrophobicity of the color-tuned 2D-NF surfaces is highly advantageous in their practical applications because π-electronic molecules, and the performance of devices based on such molecules, are influenced significantly by environmental exposure to moisture, which generally causes chemical degradation and a sharp decrease in physical stability. 35,36 Another noteworthy feature is that, when we adopted a modified soft deposition technique, 37 a thicker fabric consisting of multiple layers of different kinds of 2D-NFs could be obtained. Such heterogeneous multilayered 2D-NFs are known to be difficult to fabricate, in cases of general multilayer films or assemblies of π-electron molecules, by solution processes such as drop-casting and spin-coating techniques.…”
Section: Conformation Change Of Cn-tfmbe Molecules Duringmentioning
confidence: 99%
“…The crude mixture was chilled in the refrigerator overnight, and the precipitate product was ltered out. A white solid was obtained aer recrystallization of the crude product from diethyl ether to yield 9.26 g (65%) of (4). In a 100 mL round-bottomed ask, diethyl-3,4-dihydroxythiophene-2,5-dicarboxylate (2) (0.75 g, 2.9 mmol) was dissolved in 15 mL anhydrous DMF under inert (nitrogen) atmosphere.…”
Section: Synthesis Of 510-dihydrobenzo[f]thieno[34-b][14] Dioxocine (...mentioning
confidence: 99%
“…They are also termed as synthetic metals or intrinsically electroactive conjugated polymers. [1][2][3][4][5] The discovery of the high electrical conductivity in doped polyacetylene has stimulated an enormous amount of work towards the elucidation of the electronic properties of conjugated organic polymers. [6][7][8][9][10] Further studies revealed that they have appreciably fast charge-discharge kinetics, suitable morphology and fast doping-undoping processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental conditions and instrumentation have been described. 5 Figure 1 shows typical cyclic voltammograms (CVs) of the poly(3-methylthiophene) conducting polymer electrode in the solution studied. In the presence of DC-18C-6 significant transient 'up and down noise-like fluctuations' in the CVs occur, which, to our knowledge, have never been noticed and reported in the literature.…”
mentioning
confidence: 99%